PENINGKATAN KEMAMPUAN PENALARAN MATEMATIK SISWA KELAS VIII MELALUI PEMBELAJARAN INDUKTIF - Raden Zainal Abidin; Heris Hendriana; Wahyu Hidayat (IKIP Siliwangi, 2018)
This research is motivated by the results of previous research which shows that students' mathematical reasoning ability is not as expected. One of the lessons to improve the ability of mathematical reasoning is inductive learning. The purpose of this research is to know the improvement of students' mathematical reasoning ability as a result of inductive learning. This study is a quasi-experiment that implements two lessons namely inductive learning and conventional learning. Population in this research is a student of the junior high school in Regency of West Bandung. Sampling was done by purposive sampling and obtained two classes as research sample. The research instrument used is the test of mathematical reasoning ability. Based on the result of the analysis, it can be concluded that the improvement of mathematical reasoning ability of students who get inductive learning is better than students who get conventional learning.